2007
DOI: 10.1590/s1413-70542007000600032
|View full text |Cite
|
Sign up to set email alerts
|

Study of preparations of bee pollen extracts, antioxidant and antibacterial activity

Abstract: The aim of this study was to determine the antioxidant activity, phenolic content and antibacterial activity of pollen extracts obtained with different concentrations of ethanol. Each extraction condition (ethanol solutions from 40 to 90%) had a different effect in the phenolic compounds content. Although, the pollen extract obtained at 60, 70 and 80% of ethanol showed relatively higher levels of phenolic compounds (>10 mg/g) and did not present statistical significant difference between the extraction conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
0
14

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(118 citation statements)
references
References 20 publications
(17 reference statements)
8
85
0
14
Order By: Relevance
“…The extracts were obtained according to the methodology described by Carpes et al (2007) with modifications. Briefly, 1 g of pollen from each of the ten apiary samples was mixed together.…”
Section: Hydroethanolic Pollen Extracts (Hpe)mentioning
confidence: 99%
See 1 more Smart Citation
“…The extracts were obtained according to the methodology described by Carpes et al (2007) with modifications. Briefly, 1 g of pollen from each of the ten apiary samples was mixed together.…”
Section: Hydroethanolic Pollen Extracts (Hpe)mentioning
confidence: 99%
“…The content of total phenolic compounds was determined using the spectrophotometric method of FolinCiocalteu (FC) modified by Carpes et al (2007) using a standard curve (linear regression of the absorbance) of gallic acid (0.5-100 µg/mL). Aliquots (2.5 mL) of FC reagent were added to 0.5 mL of diluted HPE (1:100), and 5 min later, 2.0 mL of 4% (w/v) sodium carbonate were added (Na 2 CO 3 ).…”
Section: Determination Of Total Phenolicsmentioning
confidence: 99%
“…However, our results have similarity with the data obtained by Basuny et al (2013) who found that IC 50 for palm pollen extract was 0.62 mg/mL also with Carpes et al (2009) who found that IC 50 for pollen ranged from 0.8 to 4.69 mg/mL for pollen collected from Southern Brazil. Also, highest degree of antioxidant activity was found in the extraction at 60% of ethanol solution for Parana state pollen, which also showed the highest concentration of polyphenol compounds (Carpes et al, 2007). About the mixtures of propolis and pollen extracts, the IC 50 is generally moderate between pollen and propolis and this suggested that these mixtures can be used also as a potent antioxidant, which gathered the functional and pharmacological activities of both extracts.…”
Section: Resultsmentioning
confidence: 82%
“…Extracts of bee products was prepared as the method described by Vongsak et al (2015) and Carpes et al (2007) with some modifications. each bee product sample (30g) were milled, homogenized and extracted individually using 300 mL of ethanol as extraction solvent in different concentrations ( 98,70,0%) at temperature of 50ºC for 30 min with constant agitation.…”
Section: Preparation Of Bee Products Extractmentioning
confidence: 99%
See 1 more Smart Citation